FAMILY SUPPORTS IN ELDERLY HEALTH CARE AT SIMPANG TIGA PUBLIC HEALTH CARE AREA’S OF PEKANBARU CITY - SEKANI NIRIYAH, YECY ANGGRENY, (Menara Ilmu, 2019)
Family supports is an effort to help and supporting someone if necessary. In elderly period, someone will having physical, psychology and social deteriorations. If the elderly getting older, they will have physically deterioration especially physical ability so it will influence their health. Otherwise, Elderly needs the family support to their health care. The purpose of this study was to indentify the family support in health care of elderly is Simpang Tiga Public Health Care Area’s. This was a quantitative study with descriptive design. Population were the elderly family. Sample were 97 peoples which taken by purposive sampling technique. The reserach instrument was used questionnaire. The data analyze was used univariate. The result showed that majority of elderly got physical care from family was good amount 55 peoples (56,7%), got psychology care from family was good amount 56 peoples (57,7%), got social care from family was good amount 55 peoples (56,7%) and got spiritual care from family was good amount 56 peoples (57,7%). It is recommended to family with elderly too increase the health care needs especially spiritual and social needs so influence betterquality of life in elderly.Keywords : Physical Care Needs, Psychological Care Needs, Social Care Needs, Spiritual Care Ceeds.